The Role of Empowerment in Improving the Performance of Food-Based Informal Industries in Bandung Regency, West Java, Indonesia - Charina, Anne; Kusumo, Rani Andriani Budi; Hapsari, Hepi (Journal of Ecohumanism, 2024)
Informal industries are prevalent in developing countries such as Indonesia. However, due to their unofficial nature, these industries face numerous challenges, including limited access to capital, low-skilled human resources, and insufficient technology and market information necessary for business growth. This research focuses on Ciparay, Ibun, and Majalaya—three sub-districts with the highest concentration of informal industries in Bandung Regency, West Java Province, Indonesia. The study aims to analyze empowerment’s role in enhancing informal industries’ performance in Bandung Regency. A random survey was conducted with 115 food-based informal industry entrepreneurs, and data were analyzed using the PLS-SEM. Findings indicate that empowerment indirectly influences business performance through entrepreneurs’ characteristics, managerial skills, and business knowledge (b=0.445). Entrepreneurial competence among informal entrepreneurs improves with empowerment programs, leading to enhanced industry performance. Based on these results, several policy recommendations are proposed: (1) strengthening entrepreneurial attitudes through training and mentoring, (2) enhancing managerial skills through practical support, (3) expanding business knowledge through digital literacy, and (4) creating an integrated empowerment ecosystem involving government, financial institutions, and private sector. Implementing this policy is expected to support the growth of the informal industry sector, and increase the contribution of the local economy in Bandung Regency.